Trend Analysis of the Mobile Health COVID-19 Application As A Preventive Strategy in the Era of COVID-19 Pandemic in Surakarta - Aris Widiyanto; Joko Tri Atmojo; Rina Tri Handayani (Journal of Health Promotion and Behavior, 2021)
Background: Digital technology innovation is believed to increase the effectiveness of the health system's response to epidemics. Some of the potential benefits of mobile Health (mHealth) appli-cations for managing the coronavirus 2019 (COVID-19) pandemic have been explored. This study aimed to determine the trend of using mobile health applications during the COVID-19 pandemic in Surakarta, Central Java.Subjects and Method: This study was descriptive study conducted in Surakarta, Central Java, from February to August 2021. A sample of 184 subjects aged 15 to 64 years was selected in this study. Data were collected using a questionnaire through an online survey. Data were presented in descriptive-analytical form based on the characteristics of gender, age, occupation, and education.Results: The majority of study subjects were women (84.78%), with an average age (Mean= 20.61; SD= 0.12). As many as 55.98% had used the COVID-19 mobile health application. 51.45% were satisfied with the COVID-19 mobile health application service used. As many as 60.19% of the subjects felt it was faster to get information about COVID-19. 73.78% of the study subjects reported the mobile health application could improved knowledge about preventing transmission of COVID-19. As many as 71.84% reported that the application could assist in implementing health protocols.Conclusion: The mobile health COVID-19 application accelerates the dissemination of health information, increases knowledge about preventing transmission of COVID-19 and implementation of health protocols.Keywords: mobile health, COVID-19, application, prevention.Correspondence: Aris Widiyanto. School of Health Sciences Mamba’ul ‘Ulum Surakarta, Surakarta, Central Java. Email: widiyanto.aris99@gmail.com. Mobile: +628139209095.Journal of Health Promotion and Behavior (2021), 06(02): 104-111https://doi.org/10.26911/thejhpb.2021.06.02.03